HUBUNGAN PENGUASAAN KOSAKATA DENGAN KEMAMPUAN MENULIS DESKRIPSI SISWA KELAS V SD INPRES 6/75 BUKAKA KECAMATAN TANETE RIATTANG KABUPATEN BONE - Nur Ina Yatul Aini; Rukayah; Satriani DH (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study employed a quantitative approach with a correlational research design aimed at determining the relationship between vocabulary mastery and descriptive writing ability of fifth grade students at SD Inpres 6/75 Bukaka, Tanete Riattang District, Bone Regency. The type of research used was symmetrical correlational research with a simple (bivariate) correlation design. The variables in this study were vocabulary mastery (X) and descriptive writing ability (Y). The sample consisted of all fifth grade students totaling 25 students, selected using a saturated sampling technique. The data were collected through a multiple-choice test to measure vocabulary mastery and a performance test to assess descriptive writing ability. The Pearson Product Moment correlation analysis showed a correlation coefficient of r = 0.815 with a significance value of p = 0.000 (< 0.05), which indicates a very strong correlation. Thus, H1 was accepted and H0 was rejected. Based on these findings, it can be concluded that there is a positive and significant relationship between vocabulary mastery and the descriptive writing ability of fifth grade students at SD Inpres 6/75 Bukaka, Tanete Riattang District, Bone Regency.